The effect of physical load of varying intensity on the activity of liver enzymes and hepatocytes' proliferation - II Malyshev; LP Romanova; OV Vorobeva (Open Journal of Hepatology - Peertechz Publications, 2022)
Currently, the structure of mortality and morbidity in developed countries has fundamentally changed. Infectious pathology, with the exception of several viral diseases, has faded into the background, and somatic diseases have taken the main place: coronary heart disease, hypertension, gastric ulcer,